Micromorphological features revealing two new species of Portulaca (Portulacaceae) from Brazil, segregated from P. hirsutissima - Santos, Thaíla Vieira A.; Coelho, Alexa Araújo De O. Paes; Dórea, Marcos Da Costa; Santos, Francisco De Assis R. Dos; Leite, Kelly Regina B.; Oliveira, Reyjane Patrícia (Phytotaxa, 2016)
Portulaca hirsutissima (Portulacaceae) is a succulent herb occurring in open fields, sandy or rocky soil of separate Brazilian areas. On the basis of the analyses of seeds and pollen grains macro- and micromorphology, a significative variation, which is related to the distribution pattern, was found. Two new species are here proposed, described and illustrated. Portulaca giuliettiae sp. nov. occurs in Eastern Brazil, from Paraiba to Rio de Janeiro and P. goiasensis sp. nov. is restricted to the Chapada dos Veadeiros, in Central Brazil. P. hirsutissima is now to be considered as a restricted species from Minas Gerais State. A lectotype for the name P. hirsutissima is designated from a specimen preserved at P.